TATHBÎQ AL LU’BATAIN “HIMS AL FI’L" WA "AL ‘IDD WA AL TASHFÎQ" FÎ SMP PLUS CORDOVA BANYUWANGI - Istiqomah, Himatul (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
One of the problems in teaching Arabic for teachers at school is the difficulty of organizing the classroom to motivate students. These affect the results of their learnings weakly. To resolve this problem, the types of learning media were made and applied. One of the ways to apply it is the Arabic language game. In this research, the researcher applies the games "Whisper of Verb" and "Counting and Applause" in SMP Plus Cordova Banyuwangi. This research uses the qualitative approach and field in the five classes of students in the 7th grade. The results of this research indicate that: 1) The game "Whisper of Verb" was applied to upgrade the skill of listening and memorizing the verbal vocabularies. The game "Counting and Applause" was applied to upgrade memorizing about the numerical vocabularies, cardinal and ordinal. 2) The game "Whisper of Verb" was applied in four to five parts. The game "Counting and Applause" was applied individually but together. 3) The two games "Whisper of Verb" and "Counting and Applause" made teaching the Arabic language effectively and learning it fun and not boring. 4) The two games helped to enlarge students' tendencies, social intelligence, and competitive enthusiasm. Keywords: Language Game, Whisper of Verb, Counting and Applause, SMP Plus Cordova Banyuwangi.